Evidence‐Informed Audit Standard Setting: Exploring Evidence Use and Knowledge Transfer* - Hoang, Kris; Luo, Yi; Salterio, Steven E. (Contemporary Accounting Research, 2022)
ABSTRACT Academics and practitioners agree that there are substantial barriers to systematically transferring audit research knowledge to policy‐makers. We adopt a design science approach to investigate the efficacy of employing a research synthesis, embedded in an interactive process with audit standard setters, to transfer such knowledge. We identify a standard‐setting issue that, we argue, is typical of the class of problems encountered by both parties when attempting knowledge transfer. Following design science prescriptions, we evaluate the pragmatic validity of our prototype research synthesis and its creation process. We provide initial evidence (“proof of concept”) that a research synthesis process can effectively and efficiently facilitate academic research knowledge transfer to inform audit standard setters' deliberations. Finally, we provide evidence that the problem of academic research knowledge transfer in accounting standard setting and evaluation continues. Our study and findings reflect how design science facilitates change in real‐world problem contexts through research‐based proofs of concept.